MO011A RANDOMISED, DOUBLE-BLIND, PLACEBO-CONTROLLED TRIAL OF VITAMIN K SUPPLEMENTATION TO IMPROVE VASCULAR HEALTH IN KIDNEY TRANSPLANT RECIPIENTS. (6th June 2020) - Lees, Jennifer; Rankin, Alastair; Gillis, Keith; Zhu, Luke; Rutherford, Elaine; Roditi, Giles; Witham, Miles; Jardine, Alan G; Mark, Patrick
Abstract: Background and Aims: Vascular stiffness (VS) and calcification (VC) are markers of cardiovascular disease which are prevalent in kidney transplant recipients (KTR) and associated with subclinical vitamin K deficiency. We tested the hypothesis that vitamin K supplementation would reduce VS and VC in prevalent KTR in the Vitamin K for kidney Transplant Organ Recipients: Investigating vEssel Stiffness (ViKTORIES) trial. Method: In a single-centre, phase II, parallel-group, randomised, double-blind, placebo-controlled trial (ISRCTN22012044), KTR were randomised 1:1 to vitamin K (menadiol diphosphate 5mg) or placebo thrice weekly for one year. The primary outcome was between-group difference in VS (ascending aortic distensibility by cardiac magnetic resonance imaging) at 1 year by ANCOVA adjusted for the baseline value, age and duration of end-stage kidney disease. Secondary outcomes included VC (coronary artery calcium score on non-contrast computed tomography), cardiac structure and function (on cardiac magnetic resonance imaging), blood pressure, eGFR, proteinuria and quality of life. All outcomes were assessed by intention-to-treat with secondary per-protocol analyses. Missing data were multiply imputed as a sensitivity analysis for the main outcomes. The trial was conducted in accordance with the Declaration of Helsinki and was approved by the West of Scotland Research Ethics Committee 4 (Ref: 17/WS/0101). The results were combined in a meta-analysis with other published data. Results: Ninety participants were randomised to vitamin K (n=45) or placebo (n=45) and included in the analysis. Baseline demographics, clinical history and immunosuppression regimens were similar between groups: mean age 57.6 ± 9.6 years, 70% male, with median time after transplantation 7.8 (IQR 3.5 - 13.9) years. There was no impact of vitamin K versus placebo on VS after 12 months (-0.2 (-0.5 - 0.2) vs. -0.3 (-0.6 - 0.1) x10 -3 mmHg -1 ; p=0.60), nor on VC (184 (52 - 315) vs 44 (-89 - 177) units; p=0.11), nor on any other outcome measure. Medication adherence was very good in both groups (90 vs. 95%; p=0.58). Achieved power was 85%. Serious adverse events were common (vitamin K: 26.7 vs. placebo: 60.0%): all serious adverse events were classified as expected. Multiple imputation of missing data had no impact on results of VS or VC outcomes. Combining these with other published results, vitamin K supplementation has no significant observed effect on VS or VC, though with few available studies for analysis. Conclusion: In this heterogeneous cohort of prevalent KTR, vitamin K supplementation did not reduce VS or VC over 1 year. Improving vascular health in patients with established kidney disease is likely to require a multifaceted approach.